Employment factors for wind and solar energy technologies: A literature review. (May 2015) - Cameron, Lachlan; van der Zwaan, Bob
Abstract: In this paper we present an up-to-date literature review on employment opportunities associated with the deployment of renewable energy technology. We identified approximately 70 studies and data sources published over the past decade that report analysed or observed employment impacts of renewable energy growth. These publications cover many different countries and several technology options, and present widely varying results derived from distinct methodological approaches. Our first overall conclusion is that there is clear lack of authenticity of findings in this literature, since recursive referencing abounds and relatively few studies yield truly original research. When we omit non-authentic analyses, as well as those that aggregate results in a way that does not allow us to calculate 'employment factors' (defined as the number of jobs or amount of work generated per unit of electricity production capacity), the total list of references is brought to 31 independent items. Of these, only 14 references provide separate estimates of the employment factors for the stages of manufacturing and installation, respectively, as opposed to employment factors for these two activities combined. A total of 23 items provide values for operation and maintenance (O&M) employment factors. We observe significant uncertainties in quoted figures for job creation, both across and within publications.